Manfaat Loloh Don Cemcem Dalam Sistem Kesehatan Tradisional - Sutana, I Gede (JURNAL YOGA DAN KESEHATAN, 2020)
Complex problems in people's lives in the global era often cause psychological pressure which subsequently causes various disturbances in the system of human body which eventually lead to various illness. In order to return to their health level, people are in their quest for diverse alternative health medications which have minimal side effects, one of which is back to nature by consuming traditional medicine. Traditional medicine has been familiar with the life of the Indonesian people, including the Balinese in particular. In Bali, there is a traditional health system which still exists in the community known as Usadha. In Usadha, there are various types of treatment, one of which is often used by the Balinese, namely medicinal herbs or the Balinese people often call it loloh. The Republic of Indonesia Minister of Health Regulation No. 61 of 2016 concerning Empirical Traditional Health Services and the existence of the Governor of Bali Regulation No. 55 of 2019 concerning Balinese Traditional Health Services have caused loloh to revive. Loloh is now not only consumed by the local people, but has also been consumed by foreign tourists who visit Bali. One of the prima donna is loloh don cemcem which is sourced from kecemcem leaves (Spondias pinnata (Lf) Kurz). The process of making loloh don cemcem follows the traditional serving pattern with the intention that by consuming it, people will get various benefits, especially in the aspect of physical health.